Prevention of medicalization of depression : The psychological intervention - Frauca Catalán, Patricia (2019)
In recent years, the use of antidepressant drugs has increased. Amongst the reasons that have led to the increase in the use of antidepressants, are those included in the "medicalization" process, by which normal situations of life have been treated, as the only remedy, from a medical point of view. Although antidepressants are of great help, they should not be the only resource, nor the first resource in any situation, to be used for the treatment of depression. In many situations, human beings need assistance in order to rationalize and channel their emotions which, in certain situations, can easily get out of control. It is in these situations where a clinical psychologist has an important task of preventing a normal situation from turning into something considered to be pathological. Therefore, a good strategy to alleviate the "medicalization" of depression should include a greater presence of a psychologist in any healthcare team.